Thermal Degradation Characteristics and Kinetics of Oxy Combustion of Corn Residues - Poramate Sittisun; Nakorn Tippayawong; Darunee Wattanasiriwech (Advances in Materials Science and Engineering)
Thermogravimetric analysis was used to investigate oxy combustion of corncob and stover. The biomass samples were heated from ambient temperature to 900°C at different heating rates of 10, 30, and 50 K/min. Both biomass samples showed similar weight loss patterns with three zones, corresponding to dehydration, devolatilization, and char combustion, but displayed different degradation temperatures. Increasing heating rate was found to shift the degradation patterns to higher temperatures. Decomposition rates of cob and stover may have been influenced by their lignocellulosic composition. The kinetic parameters of the thermal degradation process were also determined and compared using the Flynn-Wall-Ozawa and Kissinger-Akahira-Sunose methods. Both methods were found to give similar values and patterns of activation energy against conversion fraction. The average values were found to be in similar magnitude to those reported in the literature, around 170 and 148 kJ/mol for cob and stover, respectively.